2018
DOI: 10.5430/ijhe.v7n3p197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relationships between Coaches' Organizational Justice and Leader-Member Exchange by Structural Equation Modeling

Abstract: In this study, it was aimed to determine to what extent coaches' organizational justice levels were explained by a leader-member exchange. This study was conducted by using correlational survey model and its sub-purposes were to determine the coaches' organizational justice levels and to examine the differences in organizational justice levels according to their demographics. 230 coaches participated in the study. As a result of the study, it was determined that the organizational justice level of the coaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Schools that employ organizational justice will increase the LMX. The level of organizational justice has a positive and significant relationship to the LMX (Akyel, 2018). 2) Increased Self-efficacy.…”
Section: Efforts To Implement Lmxmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools that employ organizational justice will increase the LMX. The level of organizational justice has a positive and significant relationship to the LMX (Akyel, 2018). 2) Increased Self-efficacy.…”
Section: Efforts To Implement Lmxmentioning
confidence: 99%
“…The author finds that writing about LMX leadership in educational institutions is limited to seeing the effect of several variables on the LMX (Akyel, 2018); (Fahlevi & Satrya, 2020); (Handayani, 2019) and (Nesia & Dewi, 2020). This paper describes a collection of variables that affect the LMX and are associated with its implementation in educational institutions.…”
Section: Introductionmentioning
confidence: 99%
“…They agreed that when employees view their organization and leader to be fair, their connection with their leaders is likely to improve. Likewise, additional studies found in the literature support the evidence that educational institutions that employ organizational justice increase the LMX since the level of organizational justice has a positive relationship with LMX [ 24 , 35 ]. Employees who feel appreciated and respected, are more likely to have favourable connections with their leaders.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Moreover, a positive work environment with high POJ encourages employees to interact with their leaders comfortably. This increased openness and trust makes it easier to create high-quality LMX that is marked by respect for one another, honest communication, and common objectives [ 16 , 22 , [24] , [25] , [26] , 37 ]. Based on these perspectives, therefore, the following hypothesis is established.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation